2022
DOI: 10.3390/ijms23105793
|View full text |Cite
|
Sign up to set email alerts
|

The Cell Surface Heparan Sulfate Proteoglycan Syndecan-3 Promotes Ovarian Cancer Pathogenesis

Abstract: Syndecans are transmembrane heparan sulfate proteoglycans that integrate signaling at the cell surface. By interacting with cytokines, signaling receptors, proteases, and extracellular matrix proteins, syndecans regulate cell proliferation, metastasis, angiogenesis, and inflammation. We analyzed public gene expression datasets to evaluate the dysregulation and potential prognostic impact of Syndecan-3 in ovarian cancer. Moreover, we performed functional in vitro analysis in syndecan-3-siRNA-treated SKOV3 and C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 67 publications
0
8
0
Order By: Relevance
“…Analysis of transcriptome-wide gene expression in ovarian cancer showed that ApoE is upregulated in most high-grade serous carcinomas compared to low-grade serous carcinomas (68) . On the other hand, syndecans (Sdc) are transmembrane heparan sulfate proteoglycans (69) expressed in TAM, cancer cells, and endothelial cells, and their expression is positively correlated with a macrophage gene signature across several TCGA cancer types (70) . The studies regarding the role of SDC3 and apoE in cancer development are sparse.…”
Section: Discussionmentioning
confidence: 99%
“…Analysis of transcriptome-wide gene expression in ovarian cancer showed that ApoE is upregulated in most high-grade serous carcinomas compared to low-grade serous carcinomas (68) . On the other hand, syndecans (Sdc) are transmembrane heparan sulfate proteoglycans (69) expressed in TAM, cancer cells, and endothelial cells, and their expression is positively correlated with a macrophage gene signature across several TCGA cancer types (70) . The studies regarding the role of SDC3 and apoE in cancer development are sparse.…”
Section: Discussionmentioning
confidence: 99%
“…It is unclear if the CS modifications have alternate roles when on BG, such as mediating association with ECM components as has been reported for other PGs such as NG2 68 . Other cell surface heparan sulfate proteoglycans (HSPG), such as syndecans, perlecans, and glypicans have been shown to promote cancer pathogenesis (including ovarian) and expression changes of such HSPGs have been correlated with poorer patient outcomes [69][70][71] . Additionally, aberrant regulation of heparan sulfate sulfotransferases, responsible for enzymatic modification of HS on all HS proteoglycans, has been known to affect several pathophysiological processes from inflammation, to organ development and cancer 50,72 suggesting that shifting the balance to a more HS-modified BG could be common in pathologies.…”
Section: Discussionmentioning
confidence: 99%
“…Hillemeyer L et al [ 49 ] utilized in silico analysis using the online tool TNMplot to reveal a significant upregulation of syndecan-3 mRNA in tumor tissue and metastases compared with normal tissue. At the functional level, syndecan-3 depletion impaired 3D spheroid growth and colony formation as stemness-related readouts in SKOV3 and CAOV3 cells.…”
Section: Pathophysiological Role Of Syndecans In Ovarian Cancer Tumor...mentioning
confidence: 99%